2012
DOI: 10.3390/ijms131012994
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Dynamics (MD) and Quantum Mechanics/Molecular Mechanics (QM/MM) Study on Ornithine Cyclodeaminase (OCD): A Tale of Two Iminiums

Abstract: Ornithine cyclodeaminase (OCD) is an NAD+-dependent deaminase that is found in bacterial species such as Pseudomonas putida. Importantly, it catalyzes the direct conversion of the amino acid L-ornithine to L-proline. Using molecular dynamics (MD) and a hybrid quantum mechanics/molecular mechanics (QM/MM) method in the ONIOM formalism, the catalytic mechanism of OCD has been examined. The rate limiting step is calculated to be the initial step in the overall mechanism: hydride transfer from the L-ornithine’s Cα… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 71 publications
(66 reference statements)
1
17
0
Order By: Relevance
“…[13,17]). Homologous aspartate and glutamate residues, related to cyclization [24], are not found in LhpI (and other OCD/μ‐crystallin members), confirming only Pyr2C (and/or Pip2C) reductase activity. In OCD (from P. putida ), Asp 161 forms hydrogen bonds with the 2′‐ and 3′‐hydroxyl groups of the NADH ribose moiety [13,24] (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…[13,17]). Homologous aspartate and glutamate residues, related to cyclization [24], are not found in LhpI (and other OCD/μ‐crystallin members), confirming only Pyr2C (and/or Pip2C) reductase activity. In OCD (from P. putida ), Asp 161 forms hydrogen bonds with the 2′‐ and 3′‐hydroxyl groups of the NADH ribose moiety [13,24] (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The analysis of the trajectories has shown that, after the equilibration, these criteria are met in most of the structures, hence, the entropic cost for reaching aproductive conformation should not be significant. To investigate the PES along the mechanism of the macrocyclization reaction, we performed QM/ MM calculations, widely used in enzymatic studies [15][16][17][18] applying an ONIOM scheme, [19] as implemented in the Gaussian 09 software package. [20] The system, containing at otal of 5200 atoms, was divided into a" QM layer" containing 91 atoms (Figure 1) and an "MM layer," which were treated at DFT and classical MM levels, respectively.T he high layer includes the catalytic triad [Ser783, His618 (side chain until C a ), and Asp548 (side chain until C b )], Asn717 (side chain until C g )and P1 (Cys), P1' (Ala), and P2' (Tyr) residues, and the terminal Ile of the substrate (a list of the atoms in the QM layer is given in table SI-1 in the Supporting Information).…”
Section: Computationalmethodsmentioning
confidence: 99%
“…The analysis of the trajectories has shown that, after the equilibration, these criteria are met in most of the structures, hence, the entropic cost for reaching a productive conformation should not be significant. To investigate the PES along the mechanism of the macrocyclization reaction, we performed QM/MM calculations, widely used in enzymatic studies applying an ONIOM scheme, as implemented in the Gaussian 09 software package . The system, containing a total of 5200 atoms, was divided into a “QM layer” containing 91 atoms (Figure ) and an “MM layer,” which were treated at DFT and classical MM levels, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This scheme is analogous to the oxidative deamination of l -amino acid to 2-oxo acids by AlaDH [8] , and has been preliminarily proposed based on biochemical experiments [10] . However, the crystal structure and molecular dynamic analysis of OCD [2,11] indicate an alternative mechanism (scheme II) that no attack on the iminium by water occurs: intramolecular cyclic addition of C-5 nitrogen of the iminium to the C-2 carbon to form 2-aminoproline (step 4), loss of ammonia, and reduction of the resulting imine, Pyr2C (step 5).…”
Section: Introductionmentioning
confidence: 99%
“…1 C). Interestingly, LhpI protein is a novel member of the OCD/CRYM superfamily, and catalyzes only the reduction of Pyr2C to l -proline (no OCD activity) [11] . Furthermore, there is no sequence similarity to DpkA protein as is known for the reductase of Pyr2C from bacteria [16] , strongly suggesting their convergent evolution.…”
Section: Introductionmentioning
confidence: 99%